Profil Biaya Pengobatan Serangan Asma berdasarkan Kelas Rawat Inap - Anggara Martha Pratama; Amelia Lorensia (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACTBackground of Study: Asthma is a chronic disease that requires long-term treatment. Treatment costs are one of the important things that need attention in asthma attack treatment strategies.Methods : The design of this study was non-experimental with a retrospective method, during the period January 2017 - December 2018, following the patient's medical record data. The research variable is the cost of the patient while the respondent is hospitalized. The study was conducted in a hospital in Jember City, East Java. Data collection is carried out in the data collection form, the data collection form contains the patient's identity and data on the cost of treatment while in the hospital. Then, descriptive and chi-square data analysis was carried out to see the differences between inpatient rooms.Results : The total research respondents were 99 people. Most of the respondents in all inpatient classes were at the level of mild asthma. There was no difference in the total cost of the severity of mild asthma attacks between the inpatient groups in class 2 and 3 (from the t-test with P value = 0.003), while in class 1 there is a significant difference when compared to classes 2 and 3. Meanwhile, at the moderate level of asthma attack severity, there is a significant difference when compared to classes 1 and 2.Conclusion : Most of the asthma attacks that are treated are mild and the higher the severity, the higher the cost.Keywords : cost, inpatient class, asthma attack